Lighting Improvement in Building Renovation - Syarifah Muthia Putri; Dina Maizana; Muhammad Rizal Irhami (Journal of Renewable Energy, Electrical, and Computer Engineering, 2021)
Lighting systems that are not up to standard will have an impact on eye fatigue so that the work results of the staff are not optimal. This problem can be solved by designing a lighting system according to the standards that have been determined through the results of previous studies. The 1st floor of the Faculty Engineering, Universitas Medan Area building requires lighting improvements to provide comfort to all staff and lecturers. This research was conducted by measuring the value of light intensity in each room and improving the lighting system which was analyzed through the shape of the room, the color of the walls, and the position of the lights. The results of the study provide additional light points and the position of the lamp according to the utilization.